Determination of molar mass of structured acrylic microgels: Effect of molar mass on coating properties of self-crosslinking latexes - Machotová, Jana; Podzimek, Štěpán; Zgoni, Hedvika; Šňupárek, Jaromír; Rückerová, Adéla (My University, 2016)
The film formation process of emulsion polymers may be affected seriously by introducing the self-crosslinking chemistry. In order to possess increased final coating properties, a balance between chemical crosslinking and polymer chain mobility resulting in sufficient inter-diffusion and entanglement of polymer chains during the particle coalescence stage has to be maintained, which can be tuned significantly by varying the molar mass of emulsion copolymers. The self-crosslinking latexes of core-shell microgel particles were synthesized by the emulsion polymerization of methyl methacrylate and butyl acrylate as main monomers. The particle core was slightly crosslinked using allyl methacrylate, to prevent the copolymers forming the core phase from migration into the shell phase. For inter-particle crosslinking, diacetone acrylamide was copolymerized into the shell layer of latex particles to provide sites for subsequent reaction with adipic acid dihydrazide. The molar mass of copolymers forming the shell layer was systematically reduced by isooctyl 3-mercaptopropionate included in the synthesis of shell layers. The molar mass distribution of latex particles was determined using size exclusion chromatography (SEC) and asymmetric flow field flow fractionation (A4F), respectively, both separation methods being coupled with a multi-angle light scattering (MALS) detector. Whereas SEC-MALS was found to be convenient for the characterization of low molar mass shell copolymers without crosslinked structure, A4F-MALS was proved as a very efficient technique for the characterization of high molar mass copolymers and core-shell microgels. The results described empirically the effects of molar mass of the shell layer copolymer on influencing the end-use properties of coatings.
Stanovení molekulové hmotnosti strukturovaných akrylátových mikrogelů: vliv molekulové hmotnosti na vlastnosti nátěrů na bázi samosíťujících latexů
Keywords: Emulsion polymerisation; Core-shell latex; Keto-hydrazide crosslinking; Molar mass distribution; A4F-MALS; Emulzní polymerace; core-shell latex; keto-hydrazidové síťování; distribuce molekulové hmotnosti; A4F